2003
DOI: 10.1111/j.1349-7006.2003.tb01373.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of multiple genes in gastric carcinoma: Association with histological type and CpG island methylator phenotype

Abstract: Hypermethylation of CpG islands is associated with silencing of various tumor suppressor genes. Recent studies on colorectal and gastric cancer have identified a CpG island methylator phenotype (CIMP), which involves the targeting of multiple genes by promoter hypermethylation. For determination of association between DNA methylation pattern or histological type and CIMP status in gastric carcinoma, CpG islands in the promoters of hMLH1 and CDH1 genes, CpG islands overlapping exon 1 of MGMT and p16INK4a genes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
69
2
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 26 publications
8
69
2
3
Order By: Relevance
“…Using different DNA methylation markers and different methodology, CpG island methylator phenotype was found to be associated with 'diffuse' histology in some reports 33,38 but not in others. 39,40 These controversial findings are most likely due to the use of differing DNA methylation marker panels as well as methods of analysis. In the present study, we analyzed 27 DNA methylation markers using the MethyLight technology and diffuse-type GC showed a significantly higher frequency of CpG island hypermethylation than intestinaltype GC, although the number of cases was limited.…”
Section: Methylation In Gc Was Revealed For the First Time In Thismentioning
confidence: 99%
“…Using different DNA methylation markers and different methodology, CpG island methylator phenotype was found to be associated with 'diffuse' histology in some reports 33,38 but not in others. 39,40 These controversial findings are most likely due to the use of differing DNA methylation marker panels as well as methods of analysis. In the present study, we analyzed 27 DNA methylation markers using the MethyLight technology and diffuse-type GC showed a significantly higher frequency of CpG island hypermethylation than intestinaltype GC, although the number of cases was limited.…”
Section: Methylation In Gc Was Revealed For the First Time In Thismentioning
confidence: 99%
“…13 The presence or absence of CIMP and DNA methylation of 5 genes (hMLH1, MGMT, p16 INK4a , CDH1, and RAR-beta) was determined previously. 15 …”
Section: Bisulfite Polymerase Chain Reaction (Pcr) and Methylation-spmentioning
confidence: 99%
“…13 Originally CIMP-positive GC was defined as a tumor with methylation at more than 3 loci methylated in tumors (MINT: MINT1, MINT2, MINT12, MINT25, and MINT31). 13 CIMP-positive GCs also tend to show DNA methylation of the p16 INK4a , 13 hMLH1, 15 and RIZ1 genes, 16 suggesting that CIMP is an important pathway involved in stomach carcinogenesis. However, limited numbers of genes have been shown to be associated with CIMP-positive GC, and the role of CIMP has not been clarified in detail.…”
mentioning
confidence: 99%
“…Furthermore, concurrent promoter hypermethylation of multiple genes, which is termed descriptively as the 'CpG island methylator phenotype' (CIMP), was also described in gastric cancers. 7 Although, the epigenetic changes have been accepted as an important mechanism underlying tumor onset and progression, there are limited data related to factors inducing methylation. Recent studies have indicated the existence of a mechanistic linkage between DNA methylation and infectious agents.…”
mentioning
confidence: 99%